How to measure the environmental impact of copper production - Zaror, Claudio; Vega, Mabel (Base Diseño e Innovación, 2015)
Through two Fondef projects, a team of researchers from the University of Concepción assessed the life cycle of the primary production of copper and raised how to develop a certified environmental product declaration for copper and copper products. The goal is that copper, a product so valuable to the Chilean economy, may be able to compete in increasingly demanding markets in terms of the impact that the production of a good has on the environment.